Peran Penting Efektivitas Komunikasi Dalam Persepsi Negosiasi Bisnis - Fitriana Albertina; Cecep Safa'atul Barkah; Nurillah Jamil Achmawati Novel (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2022)
In negotiations, both parties interests and benefits must be considered. Therefore, communication is the key to productive negotiations. This descriptive qualitative study employs a literature review as its methodology, namely collecting data from various previously published reference sources. According to the study, communication between two parties must convey the same meaning or message. Communication and decision-making are crucial components of negotiations. Good negotiators must possess the communication skills of clarity, precision, and persuasion. The objective of negotiation is mutual comprehension. Negotiators must avoid misunderstandings that can lead to significant communication issues. The significance of developing a desire to comprehend the background, perspective, and qualities of each negotiator for the negotiation process's success. In addition to empathy, negotiators must be able to make the best decisions and propose the best deals. The outcome of this research is that effective communication is crucial to successful negotiations that result in collective decisions.